Non-ionizing 405 nm Light as a Potential Bactericidal Technology for Platelet Safety: Evaluation of in vitro Bacterial Inactivation and in vivo Platelet Recovery in Severe Combined Immunodeficient Mice - Michelle Maclean; Michelle Maclean; Monique P. Gelderman; Sandhya Kulkarni; Rachael M. Tomb; Caitlin F. Stewart; John G. Anderson; Scott J. MacGregor; Chintamani D. Atreya (Frontiers in Medicine, 2020)
Bacterial contamination of ex vivo stored platelets is a cause of transfusion-transmitted infection. Violet-blue 405 nm light has recently demonstrated efficacy in reducing the bacterial burden in blood plasma, and its operational benefits such as non-ionizing nature, penetrability, and non-requirement for photosensitizing agents, provide a unique opportunity to develop this treatment for in situ treatment of ex vivo stored platelets as a tool for bacterial reduction. Sealed bags of platelet concentrates, seeded with low-level Staphylococcus aureus contamination, were 405 nm light-treated (3–10 mWcm−2) up to 8 h. Antimicrobial efficacy and dose efficiency was evaluated by quantification of the post-treatment surviving bacterial contamination levels. Platelets treated with 10 mWcm−2 for 8 h were further evaluated for survival and recovery in severe combined immunodeficient (SCID) mice. Significant inactivation of bacteria in platelet concentrates was achieved using all irradiance levels, with 99.6–100% inactivation achieved by 8 h (P < 0.05). Analysis of applied dose demonstrated that lower irradiance levels generally resulted in significant decontamination at lower doses: 180 Jcm−2/10 mWcm−2 (P = 0.008) compared to 43.2 Jcm−2/3 mWcm−2 (P = 0.002). Additionally, the recovery of light-treated platelets, compared to non-treated platelets, in the murine model showed no significant differences (P = >0.05). This report paves the way for further comprehensive studies to test 405 nm light treatment as a bactericidal technology for stored platelets.